English Business Slang as a Component of the Business Language (in a Comparative Aspect with Russian Business Slang) - Sh. Shakirova, Dilyara; K. Ismagilova, Gulyusa (International Journal of Criminology and Sociology, 2022)
In business dealing in an English-speaking background, you can often find some abbreviations, acronyms, and special vocabulary exceptionally related to business and business life. The present article is concerned with the problem of the formation and use of English business slang in modern English business discourse in respect of the comparative aspect with Russian-language slang. We have analyzed the following main problems: theoretical aspects of the concept of “slang”, special aspects of the study of this issue by modern linguists, the use of slang in business discourse. We have made conclusions about the compositional, structural, lexical, and semantic features of the business language, and also analyzed the role of English business slang.